Distinct Brain and Behavioral Benefits from Cognitive vs. Physical Training: A Randomized Trial in Aging Adults - Chapman, Sandra B.; Aslan, Sina; Spence, Jeffrey S.; Keebler, Molly W.; DeFina, Laura F.; Didehbani, Nyaz; Perez, Alison M.; Lu, Hanzhang; D'Esposito, Mark (Frontiers in Human Neuroscience, 2016)
Insidious declines in normal aging are well established. Emerging evidence suggests that non-pharmacological interventions, specifically cognitive and physical training, may counter diminishing age-related cognitive and brain functions. This randomized trial compared effects of two training protocols: cognitive training (CT) versus physical training (PT) on cognition and brain function in adults 56–75 years. Sedentary participants (N=36) were randomized to either CT or PT group for 3 hours/week over 12 weeks. They were assessed at baseline, mid-training and post-training using neurocognitive, MRI and physiological measures. The CT group improved on executive function whereas PT group’s memory was enhanced. Uniquely deploying cerebral blood flow (CBF) and cerebral vascular reactivity (CVR) MRI, the CT cohort showed increased CBF within the prefrontal and middle/posterior cingulate cortex without change to CVR compared to PT group. Improvements in complex abstraction were positively associated with increased resting CBF in dorsal anterior cingulate cortex. Exercisers with higher CBF in hippocampi bilaterally showed better immediate memory. The preliminary evidence indicates that increased cognitive and physical activity improves brain health in distinct ways. Reasoning training enhanced frontal networks shown to be integral to top-down cognitive control and brain resilience. Evidence of increased resting CBF without changes to CVR implicates increased neural health rather than improved vascular response. Exercise did not improve cerebrovascular response, although CBF increased in hippocampi of those with memory gains. Distinct benefits incentivize testing effectiveness of combined protocols to strengthen brain health.